R&D investment, financing constraints and corporate financial performance: Empirical evidence from China - Wang, Xiaohong; Fan, Min; Fan, Yaojun; Li, Yue; Tang, Xianghua (Frontiers in Environmental Science, 2022)
Enterprise is the main innovation force that enhances the country's independent innovation capacity, and enterprise innovation is inseparable from the investment and support of capital, technology, specialized personnel and other elements. Using Chinese A-share listed companies from 2007 to 2019 as a sample, we examine the impact of R&D investment on firm performance. It was found that R&D investment has a significant positive correlation with the performance of listed companies, and this positive correlation is more pronounced when financing constraints are lower. The mediation effect analysis shows that R&D investment can improve firm performance by boosting total factor productivity. Additional research has shown that a higher level of internal control quality can improve the boosting effect of R&D investment on firm performance. Moreover, R&D investment by SOEs can improve the performance of enterprises compared with non-SOEs. In this paper, we study the impact of R&D investment on firm performance from the perspective of funding constraints and enrich the literature on R&D investment and firm performance.